Mastermind mediates chromatin-specific transcription and turnover of the Notch enhancer complex - Fryer, Christy J. (Cold Spring Harbor Laboratory Press, 2002)
Signaling through the Notch pathway activates the proteolytic release of the Notch intracellular domain (ICD), a dedicated transcriptional coactivator of CSL enhancer-binding proteins. Here we show that chromatin-dependent transactivation by the recombinant Notch ICD–CBF1 enhancer complex in vitro requires an additional coactivator, Mastermind (MAM). MAM provides two activation domains necessary for Notch signaling in mammalian cells and in Xenopus embryos. We show that the central MAM activation domain (TAD1) recruits CBP/p300 to promote nucleosome acetylation at Notch enhancers and activate transcription in vitro. We also find that MAM expression induces phosphorylation and relocalization of endogenous CBP/p300 proteins to nuclear foci in vivo. Moreover, we show that coexpression with MAM and CBF1 strongly enhances phosphorylation and proteolytic turnover of the Notch ICD in vivo. Enhanced phosphorylation of the ICD and p300 requires a glutamine-rich region of MAM (TAD2) that is essential for Notch transcription in vivo. Thus MAM may function as a timer to couple transcription activation with disassembly of the Notch enhancer complex on chromatin.